Reduction of Postoperative Nausea and Vomiting Induced by Spinal Anesthesia: Peppermint and Lavender Aromatherapies as Complementary Therapies - Arif, Taufan; Ciptaningtyas, Maria Diah; Mudviyanti, Navalia Nailin; Solikhah, Fitriana Kurniasari (Folia Medica Indonesiana, 2024)
Highlights: 1. This study provides insight into the effectiveness of peppermint and lavender aromatherapies in reducing postoperative nausea and vomiting in patients following spinal anesthesia. 2. Aromatherapies with peppermint and lavender administered three times within six hours have demonstrated potential as an easy-to-apply intervention that reduces postoperative nausea and vomiting. 3. In terms of effectiveness, however, peppermint aromatherapy exhibits a higher effectiveness in reducing nausea and vomiting compared to lavender aromatherapy. AbstractNausea and vomiting are common occurrences after surgery with spinal anesthesia, potentially leading to complications and delayed recovery. Hypotension associated with spinal, epidural, and combined spinal-epidural anesthesia is a significant factor contributing to postoperative nausea and vomiting (PONV). This study aimed to determine the difference in effectiveness between peppermint and lavender aromatherapies for reducing PONV in patients receiving spinal anesthesia. This study used a pretest-posttest design with a control group. The research sample comprised at least 12 respondents in each group, resulting in a total of 36 respondents selected by a random sampling technique utilizing a wheel spinner. The inclusion criteria were respondents who experienced moderate to severe PONV, as indicated by scores of 9–24. The Rhodes Index of Nausea, Vomiting, and Retching (RINVR) instrument was utilized to measure the level of nausea and vomiting over six hours. The statistical analysis included the Mann-Whitney test and the Wilcoxon test, with a significance level set at p